2020
DOI: 10.3389/fmed.2020.00411
|View full text |Cite
|
Sign up to set email alerts
|

miR-214 Protects Against Uric Acid-Induced Endothelial Cell Apoptosis

Abstract: Background: Uric acid (UA) has been reported to be an important risk factor for cardiovascular diseases and can cause endothelial cell apoptosis through unclear mechanisms. Accumulating evidence has demonstrated that miR-214 plays a pivotal role in the pathogenesis of cardiovascular diseases. This study was to investigate the role of miR-214 in UA-induced endothelial cell apoptosis and the underlying mechanism. Material and methods: We enrolled 30 patients with hyperuricemia and 32 healthy controls and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Uric acid is mainly excreted in the kidney [ 36 ]. Some in vitro studies have found that PGE2 release of cells increases under the stimulation of uric acid [ 37 , 38 ]. However, these experiments were not confirmed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid is mainly excreted in the kidney [ 36 ]. Some in vitro studies have found that PGE2 release of cells increases under the stimulation of uric acid [ 37 , 38 ]. However, these experiments were not confirmed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are non-coding RNAs, 18-22 nucleotides in length, that regulate the expression of their target genes by specific binding to their 3'-UTR (10). Emerging evidence has suggested that miRNAs are involved in several cellular processes, including cell proliferation, apoptosis, differentiation and invasion (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia is considered a risk factor for a number of disorders, including diabetes mellitus, cardiovascular diseases and metabolic syndrome ( 21 ). Accumulating evidence suggests that UA can cause endothelial injury and dysfunction, though the mechanism remain unclear ( 22 , 23 ). Apoptosis induced by ox-LDL in vascular endothelial cells is an important process in the progression of atherosclerosis ( 11 ).…”
Section: Discussionmentioning
confidence: 99%